Characterizing Early Cardiac Metabolic Programming via 30% Maternal Nutrient Reduction during Fetal Development in a Non-Human Primate Model - Pereira, Susana P. (2023)
Intra-uterine growth restriction (IUGR) is a common cause of fetal/neonatal morbidity and mortality and is associated with increased offspring predisposition for cardiovascular disease (CVD) development. Mitochondria are essential organelles in maintaining cardiac function, and thus, fetal cardiac mitochondria could be responsive to the IUGR environment. In this study, we investigated whether in utero fetal cardiac mitochondrial programming can be detectable in an early stage of IUGR pregnancy. Using a well-established nonhuman IUGR primate model, we induced IUGR by reducing by 30% the maternal diet (MNR), both in males (MNR-M) and in female (MNR-F) fetuses. Fetal cardiac left ventricle (LV) tissue and blood were collected at 90 days of gestation (0.5 gestation, 0.5 G). Blood biochemical parameters were determined and heart LV mitochondrial biology assessed. MNR fetus biochemical blood parameters confirm an early fetal response to MNR. In addition, we show that in utero cardiac mitochondrial MNR adaptations are already detectable at this early stage, in a sex-divergent way. MNR induced alterations in the cardiac gene expression of oxidative phosphorylation (OXPHOS) subunits (mostly for complex-I, III, and ATP synthase), along with increased protein content for complex-I, -III, and -IV subunits only for MNR-M in comparison with male controls, highlight the fetal cardiac sex-divergent response to MNR. At this fetal stage, no major alterations were detected in mitochondrial DNA copy number nor markers for oxidative stress. This study shows that in 90-day nonhuman primate fetuses, a 30% decrease in maternal nutrition generated early in utero adaptations in fetal blood biochemical parameters and sex-specific alterations in cardiac left ventricle gene and protein expression profiles, affecting predominantly OXPHOS subunits. Since the OXPHOS system is determinant for energy production in mitochondria, our findings suggest that these early IUGR-induced mitochondrial adaptations play a role in offspring's mitochondrial dysfunction and can increase predisposition to CVD in a sex-specific way.